ОПШТЕСТВЕНАТА УСЛОВЕНОСТ НА РЕЛИГИОЗНОТО СЛИКАРСТВО ВО Р.МАКЕДОНИЈА - Dushka Matevska; Zoran Matevski (INSTITUTE FOR SOCIO-CULTURAL ANTROPOLOGY OF MACEDONIA, 2019)
Art and society exist in parallel as two different, but not separate realities. The research of the social character of art is mostly geared towards determining the social pulse that is expressed through works of art as a determining and constituent element. The work of art itself exists and acts in an unbreakable bond with at least three other basic elements: the author of the work, who even though is her own individual, still lives and acts in the context of certain social relations; the medium, or the "matter" through which the work is realized; and the consumer of the work of art. In the religious painting in R. Macedonia, the Christian Orthodox Church is the Imain censor in the choice of the themes and the ways in which they should be-spatially and stylistically fitted into the sacral objects. It has to be shown in a recognizable way so that believers can get closer to god. However, every attempt to experience religious content through painting is at the same time a risk that its absolute and mystic nature will be lost. When god is presented in a physical form, there is a risk of idolatry. The believer admires the beautiful instead of respecting the holy. In orthodox Christian art, the visual communication of frescos and icons are not so much an artistic experience as an ethical act. The meaning of religious art is to show the spiritual beauty of the inner world, not the outer beauty of the visual form s. When viewing an icon or a fresco, a layman might see a wrinkled and tortured face of some saint, but the believer discovers its spiritual beauty. The frescos and icons do hot just represent the Holy Scripture through paintings, nor are they just decorations for sacral objects. They are a manifestation of holy meanings, by equally meaningful as the holy words and rituals. The fresco and icon painters draw perfectly clean lines and apply certain colors, but in fact, they assemble sentences and write messages.
Keywords: religious painting, religious content, visual communication, holy words